Neurobiological models of emotion regulation: a meta-analysis of neuroimaging studies of acceptance as an emotion regulation strategy - Messina, Irene (Soc Cogn Affect Neurosci, 2021)
Emotional acceptance is an important emotion regulation strategy promoted by most psychotherapy approaches. We adopted the Activation Likelihood Estimation technique to obtain a quantitative summary of previous fMRI (functional Magnetic Resonance Imaging) studies of acceptance and test different hypotheses on its mechanisms of action. The main meta-analysis included 13 experiments contrasting acceptance to control conditions, yielding a total of 422 subjects and 170 foci of brain activity. Additionally, subgroups of studies with different control conditions (react naturally or focus on emotions) were identified and analysed separately. Our results showed executive areas to be affected by acceptance only in the subgroup of studies in which acceptance was compared to natural reactions. In contrast, a cluster of decreased brain activity located in the posterior cingulate cortex (PCC)/precuneus was associated with acceptance regardless of the control condition. These findings suggest that high-level executive cortical processes are not a distinctive feature of acceptance, whereas functional deactivations in the PCC/precuneus constitute its specific neural substrate. The neuroimaging of emotional acceptance calls into question a key tenet of current neurobiological models of emotion regulation consisting in the necessary involvement of high-level executive processes to actively modify emotional states, suggesting a complementary role for limbic portions of the default system.